"Please, Help Me!": Children's Perceptions of Parental Dispute as Shared in Forensic Interviews Following Alleged Maltreatment. Issue 2 (18th June 2020) - Katz, Carmit; Glucklich, Talia
Abstract : Over the last few decades, the phenomenon of child maltreatment (CM) has been recognized as a major social problem by professionals, policymakers, and researchers. Relatedly, high‐intensity parental dispute (HIPD) has been increasingly recognized, particularly in terms of its detrimental effect on the family unit and on child welfare in particular. Few studies, however, have considered these two phenomena jointly. The present study examines experiences and perceptions of children situated at their intersection. The sample comprised forensic interviews with 42 children referred to the Israeli Service of Child Forensic Interviews following alleged maltreatment. The results of a thematic analysis pointed to the centrality of children's exposure to HIPD in the context of the CM allegations for which they were referred to and about which they were asked during the interview. In addition, the analysis identified various displays of potential deficiencies in parent–child relationship in the context of HIPD and two main profiles for the disclosure of the CM allegations. The discussion stresses the exposure of the children to HIPD as a possible risk context that should receive further attention by scholars and practitioners. Moreover, it highlights the multifaceted nature of the children's experiences, which generate enormous challenges for practitioners in both clinical and forensic contexts, as well as the importance of an integrated approach that considers the HIPD context while not ignoring the CM allegations. Resumen: Durante las últimas décadas, los profesionales, los encargados de formular las políticas y los investigadores han reconocido el fenómeno del maltrato infantil como un problema social grave. Asimismo, se han reconocido cada vez más las disputas parentales de alta intensidad (DPAI), particularmente en cuanto a su efecto nocivo en el grupo familiar y en el bienestar de los niños en particular. Sin embargo, pocos estudios han considerado estos dos fenómenos en conjunto. El presente estudio analiza las experiencias y las percepciones de los niños ubicados en su intersección. La muestra estuvo comprendida por entrevistas forenses con 42 niños derivados al Servicio Israelí de Entrevistas Forenses a Menores después de supuestos maltratos. Los resultados de un análisis temático señalaron la centralidad de la exposición de los menores a las DPAI en el contexto de las acusaciones de maltrato infantil por las cuales se los derivó y sobre las cuales se les preguntó durante la entrevista. Además, el análisis identificó varias demostraciones de posibles deficiencias en la relación entre padres e hijos en el contexto de las DPAI, y dos perfiles principales para la revelación de las acusaciones de maltrato infantil. El debate acentúa la exposición de los niños a las DPAI como posible contexto de riesgo que debería recibir mayor atención por parte de académicos y profesionales. Además, destaca la índole multifacética de las experiencias de los niños, que generan enormes desafíos para los profesionales en contextos clínicos y forenses, así como la importancia de un enfoque integrado que considere el contexto de las DPAI sin ignorar las acusaciones de maltrato infantil. 摘要: 在过去的几十年里，专家、决策者和研究人员已经认定儿童虐待现象(CM)是一个主要的社会问题。与此相关的是，人们越来越认识到父母之间的高强度争执这个问题，尤其是其对家庭单位的破坏性及其特别是对儿童福利的有害影响。然而，很少有研究综合考虑到这两种现象。本研究调查了儿童在这两种现象共同出现时的经历和看法。研究样本来自于与以色列儿童法医访谈处的42名儿童的交谈记录，这些儿童经历了虐待且申诉之后转交给法医接受问询。主题分析的结果指出，在访谈中孩子们提到的和被问及的所指控的CM的情况下，儿童接触HIPD的情况处于中心地位。此外，该分析还发现了HIPD背景下亲子关系的各种潜在缺陷，以及披露CM指控的两种主要情况。讨论部分强调了儿童暴露于HIPD下是一个可能的风险环境，应该得到学者和从业者的进一步关注。此外，它强调了儿童经历的多面性，它给临床和法医领域的从业者带来了巨大的挑战，以及认识到综合方法的重要性即兼顾到HIPD背景，同时不忽视CM指控。